The Balint group and its application in medical education: A systematic review - Mohammadreza Yazdankhahfard; Fariba Haghani; Athar Omid (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: The Balint group's seminars were developed by Michael and Enid Balint for the purpose of a better understanding of doctor-patient relationships. This study aimed to introduce the Balint group and its application to the medical science educational program and to provide an up-to-date perspective on Balint group research. MATERIALS AND METHODS: The study was carried out as a systematic literature search published from January 2008 to September 2018 in the databases of PubMed, Scopus, Science Direct, and Proquest, which were searched with keywords such as the Balint group and medical education along with numerous related terms. Duplicates, non-English language articles were discarded from the review. RESULTS: A total of nine papers entered the study. Among included articles, four used a qualitative methodology, four used a quantitative methodology, and one applied a mixed methodology. Four main aims emerged from the content of papers: (1) to evaluate resident and medical student experiences in Balint groups, (2) to improve communication skills and reduce burnout level, (3) to assess the Balint group's effects on empathy, and (4) to explore the contexts and triggers of cases presented in Balint groups. CONCLUSION: Our results help us to the achievement of a better planning and design of an efficient Balint group in medical education. The findings enable the policymakers to make better decisions on the topic. Balint groups may guide medical students (residents) to become more patient centered by improving their communication skills and empathic abilities and reducing the level of burnout.